Aplasia eritroide aguda y amegacariocitosis por el lupus eritematoso sistémico - Rui Suzano; Juvenal Morais; José Fernandes; Judite Sachicumbi; Luis Caminal-Montero (Sociedade Galega de Medicina Interna, 2023)
Background - Anemia and thrombocytopenia are common features in patients with systemic lupus erythematosus (SLE). However, erythroid aplasia and amegakaryocytosis as the main physiopathological causes without other associated disorders have been rarely described. Case report - We report of a 29 y/o female with diagnosis of SLE presenting with severe anemia and thrombocytopenia due to a bone marrow immunological blockage. Patient, who initially refused transfusions, was successfully treated and had a very fast hematological response to steroids, immunoglobulin, plasma exchange, eltrombopag and rituximab. Discussion- This is an unusual case and it is possible that in this kind of patients plasma exchange associated with immunosuppressant therapy may lead to a faster, more effective and sustained recovery of the hematological disorders.